Internal load from hard training sessions is related to changes in performance after a 10-week training period in adolescent swimmers - Pind, R.; Mäestu, E.; Purge, P.; Jürgenson, J.; Arend, M.; Mäestu, J. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to investigate the association between session rating of perceived exertion (sRPE) and its categorization with the changes in swimming performance in adolescent swimmers. National level swimmers (age 16.4 ± 2.1 years, Vo2max 50.0 ± 4.0 ml/min/kg) participated in a 10-week period preceding the National Winter Championships. Pre-training and post-training physiological parameters and swimming performance were measured. All training bouts with sRPE data were recorded. In addition, trainings were categorized as light, moderate, or hard. For calculating the corresponding internal training load (ITL), 2 fixed categorizations were applied based on earlier published sources and an individualized categorization based on ventilatory thresholds. During the 10-week training period, large to very large increases were found in aerobic (effect size [ES] = 1.58) and anaerobic threshold power output W/kg (ES = 2.46), respectively, and smaller, but significant, improvement in 100-m swimming performance (ES = 0.36). Total ITL during the 10-week period was significantly related to changes in anaerobic threshold (r = 0.81). Fixed and individualized sRPE methods from hard sessions were associated with changes in Vo2max (r = 0.77) and performance of only 100-m leg kicks (r = 0.76), respectively. Internal training load was related to changes in performance variables during the 10-week study period. Using individualized sRPE values, the accumulation of the ITL from hard training sessions was associated with changes in Vo2max and swimming performance. The aforementioned categorization could help coaches in appropriate application of ITL for assessing the total training load in adolescent swimmers.